Cystoisospora spp., Contaminated Soil: The Potential Risk of Infection for the Public in the West of Iran - Mohammad Ali Mohaghegh; Mohsen Ghomashlooyan; Mohammad Reza Vafayi; Zahra Chizari; Roghiyeh Faridnia; Rasool Jafari; Mohammad Falahati; Mehdi Azami; Hamed Kalani (Hamadan University of Medical Sciences, 2015)
Cystoisospora spp., formerly known as Isospora spp., are coccidian parasitic protozoan with several species infecting a wide variety of organisms such as humans, felines and canines. This study was designed to evaluate the prevalence of Cystoisospora spp. oocysts in the soil collected from Kermanshah city, the west of Iran. One hundred and ninety-two soil samples were collected from six regions of Kermanshah city, including two regions in the city center as well as one region in each of the east, south, north and west regions. Regarding that this study was first of its kind in this region, the sampling method was according to judgmental sampling. Overall, from each region, 32 soil samples were collected, 16 of which were obtained from public parks and 16 other ones from primary schools. The Cystoisospora spp. oocysts were isolated from soil samples using the flotation method, then stained temporarily and permanently with Lugol's solution and modified Ziehl-Neelsen methods, respectively, and examined under a light microscope. Out of 192 soil samples, 15 (7.8 %) cases were infected with Cystoisospora spp. oocysts. In the public parks, the highest prevalence of oocysts was observed in the center 1 and the south regions, both with 12.5% prevalence. Moreover, in the primary school regions, the highest prevalence was observed in the center 2 (18.75 %) region followed by the east and west (both 12.5 %) regions. The findings of the present study revealed the potential of Cystoisospora spp. transmission in the west of Iran, and that the contamination of soil in primary schools was higher than public parks.